Effectiveness of Lay Health Worker Outreach in Reducing Disparities in Colorectal Cancer Screening in Vietnamese Americans - Nguyen, Bang H. (Am J Public Health, 2015)
Objectives. We conducted a cluster randomized controlled study of a lay health worker (LHW) intervention to increase colorectal cancer (CRC) screening rates among Vietnamese Americans, who typically have lower rates than do non-Hispanic Whites. Methods. We randomized 64 LHWs to 2 arms. Each LHW recruited 10 male or female participants who had never had CRC screening (fecal occult blood test, sigmoidoscopy, or colonoscopy). Intervention LHWs led 2 educational sessions on CRC screening. Control LHWs led 2 sessions on healthy eating and physical activity. The main outcome was self-reported receipt of any CRC screening at 6 months after the intervention. We conducted the study from 2008 to 2013 in Santa Clara County, California. Results. A greater proportion of intervention participants (56%) than control participants (19%) reported receiving CRC screening (P < .001). When controlling for demographic characteristics, the intervention odds ratio was 5.45 (95% confidence interval = 3.02, 9.82). There was no difference in intervention effect by participant gender. Conclusions. LHW outreach was effective in increasing CRC screening in Vietnamese Americans. Randomized controlled trials are needed to test the effectiveness of LHW outreach for other populations and other health outcomes.